Students’ Perception of LINE Webtoon Application and Its Impact on Their English Reading Habits and Skills - Maryam Sorohiti; Nurul Santika Kirsan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
Reading is one of the basic English language skills that has not been mastered by all students. On the other hand, reading media determines the frequency of reading habits and the improvement of reading skills. LINE Webtoon application, one of the digital literacy platforms, allows for comfortable and enjoyable reading on computers, tablets, and mobile devices. However, unfortunately, the LINE Webtoon application as a reading medium has not been widely used in the process of teaching and learning English reading. This study investigated students’ perceptions of using LINE Webtoon and how it influenced their English reading habits and skills. Six students from the English Language Education Department at a private university in Yogyakarta were involved. The qualitative design was applied with interviews for the data collection process. The interview results described students’ reading experience using LINE Webtoon. The findings revealed students’ interest in reading content in the app due to the attractive illustrations, the use of easy-to-understand and simple language, and the correlation of story with everyday life. The interview results also presented changes in students’ reading habits as things go about reading stories on LINE Webtoon: increasing their reading routines, reading duration, vocabulary collection, and grammar knowledge. Reading English stories through the LINE Webtoon app has positive effects on enhancing students’ reading habits and reading skills. This research implies that the development of English reading curriculum should involve various innovative and effective digital literacy platforms for the enhancement of English reading habit and skills.